2020
DOI: 10.1515/noise-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Analysing urban traffic volumes and mapping noise emissions in Rome (Italy) in the context of containment measures for the COVID-19 disease

Abstract: This study presents the result of a traffic simulation analysis based on Floating Car Data and a noise emission assessment to show the impact of mobility restriction for COVID-19 containment on urban vehicular traffic and road noise pollution on the road network of Rome, Italy. The adoption of strong and severe measures to contain the spreading of Coronavirus during March-April 2020 generated a significant reduction in private vehicle trips in the city of Rome (-64.6% during the lockdown). Traffic volumes, obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 31 publications
1
45
0
1
Order By: Relevance
“…Out of privacy concerns, we did not collect information on participant’s residential address, which thwarted linkage to existing noise maps. Even if such data were available, we could not rely on the official noise maps of Plovdiv, because of the profound and spatially variable changes observed in traffic flow and structure during the lockdown [ 23 , 140 ] and the fact that only half of the participants resided in Plovdiv in the period of interest. Moreover, typical average noise level measurements would not only underestimate participants’ actual exposure to all sources at all sites both indoors and outdoors, but also carrying out measurements at participants’ homes was not feasible during the state of emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Out of privacy concerns, we did not collect information on participant’s residential address, which thwarted linkage to existing noise maps. Even if such data were available, we could not rely on the official noise maps of Plovdiv, because of the profound and spatially variable changes observed in traffic flow and structure during the lockdown [ 23 , 140 ] and the fact that only half of the participants resided in Plovdiv in the period of interest. Moreover, typical average noise level measurements would not only underestimate participants’ actual exposure to all sources at all sites both indoors and outdoors, but also carrying out measurements at participants’ homes was not feasible during the state of emergency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the monitoring initiatives described above as an example (and many others not mentioned here) mostly report information and rely on datasets that are aggregated at city or infrastructure level [6], and based on multi-hour or daily time-averaged indicators (e.g., L den , L night , etc. ), because they take place in the framework of the Environmental Noise Directive [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the aviation sector, a recent article reported that the reduction in the number of flights was over 89% for the EU region [ 11 ]. Also, it is estimated that restrictive measures implemented by Italian authorities during the lockdown resulted in a reduction of ~64.6% in private vehicle use in Rome [ 12 ]. The Air quality in Europe—2020 report showed that NO 2 and PM 10 concentrations generally reduced across Europe as a result of lockdown measures and independently of the meteorological conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%